Improvement of element creation procedure for generating initial triangular unstructured mesh for radiative heat transfer modelling - Abal Abas, Zuraida; Salleh, Shaharuddin; Rahman, Ahmad Fadzli Nizam; Basiron, Halizah; Hasan Basari, Abd Samad; Hassim, Nurulhalim (Praise Worthy Prize, 2013)
In this paper, the methods for generating triangular unstructured mesh that follow the approach of Advancing Front Techniques (AFT) are studied. Extended Advancing Front Technique (XAFT) is also another technique that is usually used to generate triangular unstructured meshes especially in radiative heat transfer modeling. The proposed technique which called The Seven Cases Unstructured Triangulation Technique (7CUTT) is compared with the Extended Advancing Front Technique (XAFT). This paper highlights the differences resulted from the transformations with regards to its radius and the cases of consideration during element creation procedure for both techniques. The unstructured mesh generated from both techniques is then integrated with the governing equation of radiative heat transfer in order to obtain the approximation of flue gas temperature in the simplified conceptual model of ethylene furnace by using Discrete Ordinate Method (DOM) in FLUENT software. From the results, the quality of the generated mesh in the simulation using both techniques is compared.